Case Report: Familial Pseudohyperkalemia Due to Red Blood Cell Membrane Leak in a Chinese Patient - Xiong, Weijue; Song, Junxian; Yue, Zhihong; Pei, Lin; Liu, Yang; Chen, Jiangtian; Chen, Hong (Frontiers in Medicine, 2022)
Hyperkalemia is a critical condition requiring careful evaluation and timely intervention. Many conditions could manifest as pseudohyperkalemia and it’s important to differentiate them as inappropriate potassium-lowering therapy might lead to detrimental outcomes. A 56-year-old female was admitted for hyperkalemia (6.79-8.55 mmol/L). She had no symptoms or signs of hyperkalemia. A comprehensive work-up of hyperkalemia retrieved no valuable findings. Her blood samples underwent incubation tests at different temperatures and revealed temperature-dependent potassium leaks from red blood cells. Based on all test results, a diagnosis of hyperkalemia caused by red blood cell membrane defects was suspected. Whole-genome sequencing revealed a heterozygous c.1123C>T (p. R375W) mutation in the ABCB6 gene and confirmed the diagnosis of familial pseudohyperkalemia (FP). FP is an inherited benign condition in which red blood cells have increased cold-induced permeability to potassium. The patient was discharged with no additional treatment and she was suggested avoiding blood donation.